African American Firsts in Science & Technology - Julia Gelfand (Issues in Science and Technology Librarianship, 2000)
The article reviews the book African American Firsts in Science & Technology. Farmington Hills, MI: Gale, 1999. ISBN 0-7876-3876-5 by Raymond B. Webster.